Ã˜ÂªÃ˜Â¯Ã˜Â±Ã™Å Ã˜Â³ Ã˜Â§Ã™â€žÃ™â€¦Ã™ÂÃ˜Â±Ã˜Â¯Ã˜Â§Ã˜Âª Ã˜Â¨Ã˜Â§Ã˜Â³Ã˜ÂªÃ˜Â®Ã˜Â¯Ã˜Â§Ã™â€¦ Ã˜Â§Ã™â€žÃ˜Â£Ã™ÂÃ™â€žÃ˜Â§Ã™â€¦ Ã˜Â§Ã™â€žÃ™Æ’Ã˜Â±Ã˜ÂªÃ™Ë†Ã™â€ Ã™Å Ã˜Â© Ã™ÂÃ™Å Ã˜Â§Ã™â€žÃ˜Â¬Ã˜Â§Ã™â€¦Ã˜Â¹Ã˜Â© Ã˜Â§Ã™â€žÃ™â€¡Ã™â€žÃ˜Â§Ã™â€ž Ã˜Â³Ã˜Â¬Ã™â€žÃ™Å - Rahmi, Syarifah ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2020)
Cartoon films are fun and simple art that is accomplished in the hands of children through colorful cardboard papers that are drawn and cut into parts and affixed to each other, then revived by photography and animation, and these drawings are stories from the lives of children and their dreams or stories that narrate the weave of their own imagination to finally end Animated film.So I found the problems in Al Hilal Colledge, that the teacher is unable to attract the attention of students during education and cannot excel students in the subject that he will teach, the poor preparation of Arabic language teachers in the teaching process, and his ignorance of teaching methods even the most students who are forced to absorb the Arabic language. As for the appropriate and interesting way in teaching Arabic to students, it is the teaching of vocabulary using animated films to help students understand educational materials in relationships and interconnections with their daily lives in terms of individual, societal and cultural in order to obtain what he wants from education.As for the research aims for this research, it is to find out the response of students using cartoon films at Al-HilalColledge. And to know the effect of using animated films on teaching vocabulary using a descriptive and qualitative approach. And to analyze the results using statistical analysis.